An Analysis of Indirect Illocutionary Act Found in Candace Owens Podcast Entitled Becoming Brigitte: the Epilogue - Ni Nyoman Intan Airma Prawitri; Ni Made Verayanti Utami (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2025)
This study focuses on indirect illocutionary acts found in a podcast titled “Becoming Brigitte: The Epilogue” by Candace Owens. The theory used in this study is Searle’s theory. In this podcast, the researcher identified twenty-eight instances containing indirect illocutionary acts. Of these twenty-eight instances, twenty were assertive acts in interrogative form, and eight were assertive acts in expressive form. Assertive speech acts were most frequently found because this podcast is a political commentary and personal opinion, which aims to convey beliefs and influence listeners through statements that the speaker believes to be true. This study only focuses on indirect illocutionary acts because by studying indirect illocutionary acts, we can recognize the meaning behind what someone says, even if their intentions are not explicitly stated. The method used in this study is a qualitative descriptive method. The data results in this study are presented in table form and explained by presenting the data that has been found.